2017
DOI: 10.1016/j.tvjl.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Inertial sensor-based system for lameness detection in trotting dogs with induced lameness

Abstract: Lameness detection can be challenging in dogs, as reflected in the reported low inter-rater agreement when visually assessing lameness. The aim of this study was to use an inertial sensor-based system to detect and quantify induced distal and proximal limb disturbances mimicking supporting and swinging limb lameness in dogs trotting on a treadmill by measuring vertical head and pelvic movement symmetry. Ten clinically sound dogs were equipped with inertial measurement units that were attached to the head, pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…The gait profile may be affected by the mounting position and orientation of the sensor. Rhodin et al attached the sensor on the metacarpal bones [ 15 ]. It was shown that inconsistent marker placement for video motion-capture systems contributed the greatest source of variability in human gait test centers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gait profile may be affected by the mounting position and orientation of the sensor. Rhodin et al attached the sensor on the metacarpal bones [ 15 ]. It was shown that inconsistent marker placement for video motion-capture systems contributed the greatest source of variability in human gait test centers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of canine IMU gait studies has relied on a single device attached dorsally or ventrally to the chest, back, or neck of the dog to measure bouncing and swaying of the body during motion [ 7 , 8 , 9 , 10 , 11 ]. Alternatively, several studies have analyzed canine gait by one or more limb-mounted IMUs [ 12 , 13 , 14 , 15 ]. Limb-mounted techniques directly quantify metrics such as step phase durations, joint motions, and gait type.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse gait-analysis technologies have been developed and used in humans and sport horses over the past 40 years, and are constantly being refined to provide reliable measures of improvement from disease [97]. Current technologies include wearables, inertial measurement units or accelerometers which are lightweight, wireless devices to investigate activity levels, gait patterns and fitness parameters for humans and other animals [98][99][100]. Real-time or delayed-time parameters that can be analysed include ground reaction forces and foot-pressure distribution, the kinematics of joints and segments, along with dynamic electromyograms [101].…”
Section: Diagnostic and Prognostic Tools For Understanding Mechanismsmentioning
confidence: 99%
“…These sensors have also been used in horses for lying behaviour [ 15 ] and in wild animals for tracking behaviour [ 16 ]. In dogs, accelerometers have been used to monitor amount of activity [ 17 21 ], activity types [ 22 ], cognitive dysfunction [ 23 , 24 ] and for lameness detection [ 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of disease by the owner may enable them to present their dog to their veterinarian in an early stage of the disease, which could lead to more effective treatment and thus benefit the animal’s health and welfare. Accelerometers are able to detect changes in specific activities or behaviours, indicating signs linked to possible adverse health events [ 24 , 25 ]. Triaxial accelerometers can detect behavioural states by measuring accelerations in three axes, which can be analysed resulting in description of motion in different planes.…”
Section: Introductionmentioning
confidence: 99%